2013
DOI: 10.4103/2229-516x.112234
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor: The first approved reversible oral antiplatelet agent

Abstract: Platelet aggregation plays an important role in the pathophysiology of acute coronary syndrome (ACS). Aspirin is the most widely used antiplatelet agent and acts by inhibiting thromboxane A2-induced platelet activation. But it does not prevent platelets activation and aggregation by other signaling pathways like adenosine diphosphate (ADP) and Glycoprotein IIb/IIIa. Ticagrelor is the first oral reversible ADP (P2Y12) receptor antagonist. As compared to clopidogrel, ticagrelor has rapid onset as well as offset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Schindler et al have reported that, using the AT1-receptor antagonist candesartan in patients with severe atherosclerosis after superficial femoral artery stenting produces a significantly better effect against restenosis than the treatment with the ACE inhibitor quinapril [44] . Goel et al have found that Ticagrelor, a P2Y12 antagonist, prevents restenosis by inhibiting the inflammation induced by the P2Y12 receptor [45] . Wong et al have shown that PAR4 inhibition has the potential therapeutic advantage of antithrombotic activity with a low bleeding risk [46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schindler et al have reported that, using the AT1-receptor antagonist candesartan in patients with severe atherosclerosis after superficial femoral artery stenting produces a significantly better effect against restenosis than the treatment with the ACE inhibitor quinapril [44] . Goel et al have found that Ticagrelor, a P2Y12 antagonist, prevents restenosis by inhibiting the inflammation induced by the P2Y12 receptor [45] . Wong et al have shown that PAR4 inhibition has the potential therapeutic advantage of antithrombotic activity with a low bleeding risk [46] .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, to confirm that the methodology is a good approach for a particular group of patients would require extensive studies involving a large number of patient populations; we are addressing this goal in ongoing efforts. Regardless of these limitations, our studies compared cilostazol with aspirin, in contrast to previous studies, which have focused on the additional inhibition of platelet aggregation by cilostazol when co-administered with aspirin and clopidogrel [44][45][46][47] . Therefore, these data warrant a larger scale prospective randomized controlled trial for patients with aspirin intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical drugs take advantage of pathway specificity for platelet activation. For example, ticagrelor inhibits platelet activation by inhibiting ADP signaling through the P2Y12 receptor but not through other receptors (Goel, 2013;Patel et al, 2013;von Kugelgen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are clinical drugs which take advantage of pathway specificity for platelet activation. For example, ticagrelor inhibits platelet activation by thromboxane-A2, but does not inhibit their activation with ADP or collagen (4547).…”
Section: Discussionmentioning
confidence: 99%